2015
DOI: 10.1590/1678-457x.6541
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in different cocoa (Theobroma cacao, L) cultivars during fermentation

Abstract: Dne component that contribute to the flavor and aroma of chocolate are the polyphenols, which have received much attention due to their beneficial implications to human health. Besides bioactive action, polyphenols and methylxantines are responsible for astringency and bitterness in cocoa beans. Another important point is its drastic reduction during cocoa processing for chocolate production and the difference between cultivars. Thus, the present study aimed to evaluate the modifications in monomeric phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
0
21
1
1
Order By: Relevance
“…TCC in this study was higher than the TCC reported in other studies. For example, Cruz et al (2015) found a TCC without fermentation of 1.48-2.46 mg/g, which is more than 50% lower than the results obtained by the 4 min MAE in the present study; while the 10 min MAE produced the highest quantity of catechin. This result agrees with previous studies (Pervauzunalic et al 2006) and may indicate that longer extraction times produce higher quantities of TCC.…”
Section: Total Catechin Content (Tcc)contrasting
confidence: 92%
“…TCC in this study was higher than the TCC reported in other studies. For example, Cruz et al (2015) found a TCC without fermentation of 1.48-2.46 mg/g, which is more than 50% lower than the results obtained by the 4 min MAE in the present study; while the 10 min MAE produced the highest quantity of catechin. This result agrees with previous studies (Pervauzunalic et al 2006) and may indicate that longer extraction times produce higher quantities of TCC.…”
Section: Total Catechin Content (Tcc)contrasting
confidence: 92%
“…Early work has suggested that decreased concentrations of polyphenols, methylxanthines, and anthocyanin precursors in the cotyledon are associated with this observation 40 42 . Polyphenols and methylxanthines are responsible for the astringency and bitterness detected in cacao beans 43 , and it is thought that the modification of these compounds during the process of fermentation contributes to the final flavor of a chocolate 43 . In fact, during the process of fermentation, the concentration of polyphenols is reduced by up to 70% 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Early work has suggested that decreased concentrations of polyphenols, methylxanthines and anthocyanin precursors concentration in the cotyledon are associated with this observation [29][30][31] . Polyphenols and methylxanthines are responsible for the astringency and bitternes detected in cacao beans 32 , and it is thought that the modification of these compounds during the process of fermentation contributes to the final flavor of chocolate 32 . In fact, during the process of fermentation, the concentration of polyphenols is reduced by up to 70% 33 .…”
mentioning
confidence: 99%